Drowning in Information and Thirsting for Knowledge: The Information Professional’s Dilemma - Entsua-Mensah, Clement (Ghana Library Journal, 1999)
Mr. Chairman, Immediate Past President of the Ghana Library Association, Distinguished Council Members, Professional Colleagues, Invited Guests and Our friends from the Media Houses, it is indeed an honour and a privilege to address you as the 14th President of the Ghana Library Association since the Association was inaugura ted in 1962. However, this is the third in the Association’s history that a Presidential Inaugural lecture is being delivered since it was instituted in 1993 by Mr. E.S. Asiedu.